Daily foraging routines in food-caching mountain chickadees are associated with variation in environmental harshness. (September 2018) - Pitera, A.M.; Branch, C.L.; Bridge, E.S.; Pravosudov, V.V.
Abstract : Small birds overwintering in cold climates must meet the daily challenge of accumulating sufficient energy reserves throughout the day to ensure overnight survival. Theoretical work suggests that risk of starvation is a major force shaping optimal daily foraging routines. Animals are predicted to adjust how they distribute their daily foraging activity in relation to environmental harshness, which largely determines the risk of starvation. Here, we used radiofrequency identification (RFID)-enabled bird feeders to test whether mountain chickadees, Poecile gambeli – small, resident, food-caching birds – exhibited different daily foraging routines in harsher (higher elevation) versus milder (lower elevation) environments in the Sierra Nevada. In addition, we assessed foraging routines between four different periods of the nonbreeding season ranging from autumn (milder conditions) to winter and early spring (harsher conditions) and to late spring (milder conditions). We also tested whether individual variation in spatial cognition associated with food caching, which represents a more reliable food source that can be expected to lower risk of starvation, is associated with differences in daily foraging routines. Chickadees from both elevations distributed their daily foraging efforts differently throughout the nonbreeding season, consistent with theoretical predictions for milder and harsher conditions. Differences between chickadees from high and low elevations were especially pronounced during harsher winter periods, with chickadees from high elevations showing a bimodal daily routine, while low-elevation birds showed an inverted U-shaped daily routine, with most foraging during the middle of the day. Finally, significant differences in daily routines were associated with variation in spatial learning and memory performance. Overall, our study shows that daily foraging routines are consistent with risk of starvation under different degrees of environmental harshness, whether across nonbreeding seasons or between elevations, and that perception of harshness may be associated with cognitive abilities. Highlights: Chickadees exhibit different daily foraging routines across the nonbreeding season. Chickadees at high and low elevations exhibit different daily foraging routines. Elevation-related differences were especially pronounced in winter. Perception of environmental harshness may be associated with cognitive abilities.